Patient-centered medical education: A proposed definition. (3rd August 2019) - Hearn, Jasmine; Dewji, Mohamed; Stocker, Claire; Simons, Greg
Abstract: Multiple papers have been presented to define patient-centered care, with regulatory bodies such as the General Medical Council mapping this in their professional standards. Educational institutions clearly value instilling appreciation of patient-centredness in medical training, and attempts have been made to make medical education more patient-centered in practice. Such attempts are often limited to expert patients sharing personal stories, and public involvement in teaching. Despite the drive towards patient-centered care and medical education, there has been no attempt to formally define what patient-centered medical education is and what it means to medical educators globally. This paper proposes a definition of patient-centered medical education that is about the patients, with the patients, and for the patients, to ensure current and future doctors remain sensitive to all of the needs of the people they care for. This should be considered at both the micro and macro community levels.